Increasing Returns, Imperfect Competition, and Factor Prices - Epifani, Paolo; Gancia, Gino (The Review of Economics and Statistics, 2006)
We show how, in general equilibrium models featuring increasing returns, imperfect competition, and endogenous markups, changes in the scale of economic activity affect the income distribution across factors. Whenever final goods are gross substitutes (gross complements), a scale expansion raises (lowers) the relative reward of the scarce factor or the factor used intensively in the sector characterized by a higher degree of product differentiation and higher fixed costs. Under very reasonable hypotheses, our theory suggests that scale is skill-biased. This result provides a micro foundation for the secular increase in the relative demand for skilled labor. Moreover, it constitutes an important link among major explanations for the rise in wage inequality: skill-biased technical change, capital-skill complementarities, and international trade. We provide new evidence on the mechanism underlying the skill bias of scale.